2022
DOI: 10.1002/epi4.12570
|View full text |Cite
|
Sign up to set email alerts
|

One‐year cost‐effectiveness of callosotomy vs vagus nerve stimulation for drug‐resistant seizures in Lennox‐Gastaut Syndrome: A decision analytic model

Abstract: Lennox-Gastaut syndrome (LGS) is a severe form of epilepsy characterized by childhood onset, multiple drugresistant seizure types, and long-term poor prognosis. 1 Given the difficulty controlling seizures in LGS, vagus nerve stimulation (VNS) and corpus callosotomy (CC) are both often considered palliative surgical options. 2 However, there is no current consensus about which procedure is superior or what procedure should be performed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Interestingly, while other device companies have invested in transcutaneously rechargeable pulse generators, this is not yet available for children with VNS. Investing in this technology would make VNS not only more cost-effective, 33 but also safer, as our results demonstrate.…”
Section: Discussionsupporting
confidence: 60%
“…Interestingly, while other device companies have invested in transcutaneously rechargeable pulse generators, this is not yet available for children with VNS. Investing in this technology would make VNS not only more cost-effective, 33 but also safer, as our results demonstrate.…”
Section: Discussionsupporting
confidence: 60%
“…However, other studies have found similar effectiveness for both treatments 5,9,10 . Additionally, VNS seems more cost‐effective 1 year after surgery and is associated with fewer complications 4,10,11 . However, this study did not evaluate long‐term cost‐effectiveness (considering the need for VNS battery replacement), which may prove CC is more cost‐effective.…”
Section: Discussionmentioning
confidence: 80%
“…The number of trial‐based and model‐based economic evaluations was n = 7 (39%) and n = 11 (61%), respectively. More specifically, different types of model‐based economic evaluations were performed: decision tree modeling ( n = 4, 22%) 22,23,33,37 and Markov modeling ( n = 7, 39%) 20,21,24,26,30,32,36 . Two model‐based studies compared two nonpharmacological interventions (i.e., one compared KD and VNS and another compared DBS and VNS) with CAU 21,24 .…”
Section: Resultsmentioning
confidence: 99%
“…Six of those compared epilepsy surgery with CAU (i.e., ASM treatment), of which two were focused on children, one on both adults and children, and three on adults solely. One study assessed the cost‐effectiveness of epilepsy surgery via corpus callosotomy in children by comparing it to VNS using a decision‐analytic model 21 . One study assessed the cost‐effectiveness of a new minimally invasive epilepsy surgery technique, MRgLITT, with the conventional epilepsy surgery in adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation